IMPLEMENTASI GOOD CORPORATE GOVERNANCE (GCG) DALAM PENGELOLAAN DAN PERTANGGUNGJAWABAN KEUANGAN PADA PERUSAHAAN PROPERTI - Naura Abelia Diva Larasati; Dyah Ratnawati (CV. Denasya Smart Publisher, 2026)
This study evaluates the implementation of Good Corporate Governance (GCG) in the financial management and accountability of a property company. Using a descriptive qualitative approach, data were collected through interviews, direct observation, and document review related to the recording and reporting of cash disbursements. Thematic analysis was used to identify dominant patterns in the findings. Transparency is achieved through recording cash disbursements in accordance with the budget, supported by valid transaction evidence. This allows access for authorized internal parties. Accountability is reflected in an organized recording and reporting system, including multi-level approvals and verification. Adherence to standard operating procedures, independence in financial decision-making, and equitable division of tasks reinforce orderly management. Internal controls and regular assessments ensure the accuracy and reliability of financial data. Overall, GCG implementation functions effectively and enhances the company's management standards and financial accountability..